2011
DOI: 10.1080/10669868.2011.626988
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of Personal Factors in Studying Students' Perception of Sales Profession in Poland

Abstract: Since Poland has become a member of the European Union, free market activities have increased dramatically. The purpose of this study is to explore university students' perceptions of personal selling as a career in Poland. Using logistic regression and Z-test methodologies, we analyzed the perceptions of 114 students. The results confirm the findings of previous studies that personal factors play a significant role in predicting students' perception of sales profession as a career. The findings presented in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 12 publications
(16 reference statements)
0
16
0
1
Order By: Relevance
“…A comprehensive review of the literature found that attitudes towards a sales career has been a subject of interest to marketing educators and researchers for more than sixty years with numerous studies reporting negative views of sales as a career, (Mason, 1965;Paul and Worthing, 1970;Dubinsky, 1980;Honeycutt et al, 1999;Wiles and Spiro, 2004;Caballero and Joonas, 2009;Waldeck et al, 2010;Bahhouth et al, 2011, Agnihotril et al, 2014. It is thought that these negative perceptions of sales people may have emerged during a period often referred to as the 'sales era' when aggressive attempts were used by organizations to sell their products in a cutthroat competitive environment where supply exceeded demand (Kerin et al, 2009).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A comprehensive review of the literature found that attitudes towards a sales career has been a subject of interest to marketing educators and researchers for more than sixty years with numerous studies reporting negative views of sales as a career, (Mason, 1965;Paul and Worthing, 1970;Dubinsky, 1980;Honeycutt et al, 1999;Wiles and Spiro, 2004;Caballero and Joonas, 2009;Waldeck et al, 2010;Bahhouth et al, 2011, Agnihotril et al, 2014. It is thought that these negative perceptions of sales people may have emerged during a period often referred to as the 'sales era' when aggressive attempts were used by organizations to sell their products in a cutthroat competitive environment where supply exceeded demand (Kerin et al, 2009).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…However, it is thought that university students may still hold negative stereotypes (Bahhouth et al, 2011) influenced by external parties. i.e.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Estos estereotipos negativos no están restringidos a un único entorno sociocultural. Estudios realizados en diferentes entornos y países, encontraron que la venta no es considerada entre los universitarios como una carrera profesional atractiva (Lee, Sandfield y Dhaliwal, 2007;Barat y Spillan, 2009;Canales, 2012;Agnihotril, Bonney, Dixon, Erffemeyer, Pullins, Sojka y West, 2014), algo que ocurre incluso en países en vías de desarrollo como Ghana (Bahhouth, Spillan y Mensah, 2013).…”
Section: Percepción De La Actividad Comercial En El Sector Turísticounclassified